2020
DOI: 10.1371/journal.pone.0231823
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of a new expandable intramedullary nail and conventional intramedullary nails for femoral osteosynthesis in dogs

Abstract: Intramedullary nailing of diaphyseal femoral fractures is a commonly used treatment method in dogs because of its biological and biomechanical advantages compared to bone plating. To achieve adequate resistance of the intramedullary nail against torsional and axial compressive forces, additional application of transcortical screws is needed. As these interlocking screws represent a frequent cause of post-operative complications, a new expandable intramedullary nail (EXPN) was developed, which was designed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In previous biomechanical studies conducted with some expandable nail designs (41,42), these were found to be insufficient in respect of rotational loading compared to locking nails. In contrast, there are also studies showing that resistance to rotational loading is similar to that of classic nails and resistance to compressive loading is weak (43). Bekmezci et al (8) recommended that therefore, non-locking nails should not be used in multi-fragmented fractures and metaphyseal region fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous biomechanical studies conducted with some expandable nail designs (41,42), these were found to be insufficient in respect of rotational loading compared to locking nails. In contrast, there are also studies showing that resistance to rotational loading is similar to that of classic nails and resistance to compressive loading is weak (43). Bekmezci et al (8) recommended that therefore, non-locking nails should not be used in multi-fragmented fractures and metaphyseal region fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors advocate that static locking is appropriate for the prevention of rotation and shortening (44). By limiting micro-movement, static locking provides length of the fracture line and rotation is prevented (43). Static locking controls loading, shortening and rotation, but as stress is reduced in the fracture line, bone union is slowed down and osteolysis develops (44).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the internal diameters of the screws/bolts used in Groups 2 and 3 (3.2 mm) compared to Group 1 (2.4 mm) infer a marked increase in the area moment of inertia (AMI) of the screws, justifying such an event [28]. Plenert [29] demonstrated greater resistance of the sets formed by nails interlocked with screws of increased diameter in compression and torsion tests. Despite the methodological differences, both studies used supraphysiological loads, which does not invalidate the sets’ ability to be resistant enough in a hypothetical clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary nail: the past, present and the future -a review exploring where the future may lead us Orthopedic Reviews 5) was tested in an animal study in Germany. 27 This IMN featured expandable segments and bridging elements but proved to be weaker in neutralizing axial compressive forces when compared to traditional solid IMNs. 27 However, common to all expandable IMN designs, the challenge faced is removing the nail when complications do arise.…”
Section: Figure 2 Illustration Of Fixion Imn -A Cross-section Of a Long Bone Pre-and Post-expansion 19mentioning
confidence: 99%
“…27 This IMN featured expandable segments and bridging elements but proved to be weaker in neutralizing axial compressive forces when compared to traditional solid IMNs. 27 However, common to all expandable IMN designs, the challenge faced is removing the nail when complications do arise. However, no studies have been conducted or reported on the ease of removing these novel expandable IMNs if required at a later stage.…”
Section: Figure 2 Illustration Of Fixion Imn -A Cross-section Of a Long Bone Pre-and Post-expansion 19mentioning
confidence: 99%